Answer:
Choice 4 is the correct answer
たはたらさあらたはたはあらたさらやたはまさらたはまりあはらたはたさたはあらあらたはたひたはらたら、らま、らま、らまはたはたはさまらたらまはあはあらたはたひまひはたらたはまはたらまはた
Answer:
(2,6)
Step-by-step explanation:
Factor
(x+7)(x-2)
Proof
7-2=5
7*-2=-14
Zeros
x+7=0
x=-7
x-2=0
x=2
Final answer: C
Answer:
![\frac{2*x - 2}{2*x} - \frac{3*x + 2}{4*x} = \frac{x - 6}{4*x}](https://tex.z-dn.net/?f=%5Cfrac%7B2%2Ax%20-%202%7D%7B2%2Ax%7D%20%20-%20%5Cfrac%7B3%2Ax%20%2B%202%7D%7B4%2Ax%7D%20%3D%20%5Cfrac%7Bx%20-%206%7D%7B4%2Ax%7D)
Step-by-step explanation:
We have the expression:
![\frac{2*x - 2}{2*x} - \frac{3*x + 2}{4*x}](https://tex.z-dn.net/?f=%5Cfrac%7B2%2Ax%20-%202%7D%7B2%2Ax%7D%20%20-%20%5Cfrac%7B3%2Ax%20%2B%202%7D%7B4%2Ax%7D)
The first thing we want to do, is to have the same denominator in both equations, then we need to multiply the first term by (2/2), so the denominator becomes 4*x
We will get:
![(\frac{2}{2} )\frac{2*x - 2}{2*x} - \frac{3*x + 2}{4*x} = \frac{4*x - 4}{4*x} - \frac{3*x + 2}{4*x}](https://tex.z-dn.net/?f=%28%5Cfrac%7B2%7D%7B2%7D%20%29%5Cfrac%7B2%2Ax%20-%202%7D%7B2%2Ax%7D%20%20-%20%5Cfrac%7B3%2Ax%20%2B%202%7D%7B4%2Ax%7D%20%3D%20%5Cfrac%7B4%2Ax%20-%204%7D%7B4%2Ax%7D%20%20-%20%5Cfrac%7B3%2Ax%20%2B%202%7D%7B4%2Ax%7D)
Now we can directly add the terms to get:
![\frac{4*x - 4}{4*x} - \frac{3*x + 2}{4*x} = \frac{4*x - 4 - 3*x - 2}{4*x} = \frac{x - 6}{4*x}](https://tex.z-dn.net/?f=%5Cfrac%7B4%2Ax%20-%204%7D%7B4%2Ax%7D%20%20-%20%5Cfrac%7B3%2Ax%20%2B%202%7D%7B4%2Ax%7D%20%3D%20%5Cfrac%7B4%2Ax%20-%204%20-%203%2Ax%20-%202%7D%7B4%2Ax%7D%20%20%3D%20%5Cfrac%7Bx%20-%206%7D%7B4%2Ax%7D)
We can't simplify this anymore